Human trafficking and severe mental illness: an economic analysis of survivors' use of psychiatric services. Issue 1 (December 2016) - Cary, Maria; Oram, Siân; Howard, Louise; Trevillion, Kylee; Byford, Sarah
Abstract Background Previous studies have found a high prevalence of depression and post-traumatic stress disorder (PTSD) among survivors of human trafficking. European countries are required to assist trafficked people in their psychological recovery, but there are no rigorous data on the costs of doing so. The objectives of this study were to quantify the use of secondary mental health services by survivors of human trafficking; to estimate the cost of survivors' use of secondary mental health services provided by the UK National Health Service (NHS); and to identify factors that predict higher costs of mental health service provision. Methods Historical cohort study of psychiatric patients who had experienced human trafficking. The South London and Maudsley NHS Trust (SLaM) Biomedical Research Centre Case Register Interactive Search (CRIS) database was used to identify anonymised full patient records of patients who had experienced human trafficking and who had accessed SLaM mental health services between 2007 and 2012. Data were extracted on socio-demographic and trafficking characteristics and contacts with mental health services. Total costs were calculated by multiplying each resource use item by an appropriate unit cost. Factors that predicted high mental health service costs were analysed using regression models. Results One hundred nineteen patients were included in the analysis. Mean total mental health service costs per patient were £27, 293 (sd 80, 985) and mean duration of contact with services was 1490 (sd 757) days (approximately 4 years). Regression analysis showed that higher costs were associated with diagnosis of psychotic disorder (p  < 0.001) and experiences of pre-trafficking violence (p  = 0.06). Patients diagnosed with psychotic disorders cost approximately £32, 635 more than patients with non-psychotic disorders/psychological distress but no formal diagnosis and patients whose clinical notes documented pre-trafficking violence cost £88, 633 more than patients for whom pre-trafficking violence was not documented. Conclusions Trafficked patients' use of mental health services – and the cost of providing care – is highly variable, but patients with psychotic disorders and with experiences of pre-trafficking violence are likely to require more intensive support. Evidence is needed on the effectiveness of interventions to promote the recovery of survivors of human trafficking.